Hemodynamic stability during laryngeal electromyography procedures. (3rd October 2017) - Lu, Yi-An; Pei, Yu-Cheng; Wong, Alice MK; Chiang, Hui-Chen; Fang, Tuan-Jen
Abstract: Background: Laryngeal electromyography (LEMG) is accepted as safe, with minimal side effects. However, patient hemodynamic stability, during these procedures, has not been reported. This study aimed to investigate the hemodynamics in patients undergoing LEMG and determine the risk factors for hemodynamic changes. Methods: We recruited 89 consecutive patients who underwent LEMG. Baseline and postprocedural changes in vital signs were analyzed. Results: Diastolic blood pressure (DBP) increased from 75.08 ± 11.54 mmHg preprocedure to 77.4 ± 11.91 mmHg postprocedure ( p  = .006); pulse rate (PR) increased from 78.1 ± 13.3 beats per minute preprocedure to 80.02 ± 13.69 postprocedure ( p  = .027). Systolic blood pressure (SBP) and oxygen saturation were unchanged after the procedure. However, about 17% of patients experienced profound changes in vital signs of >20% above baseline during LEMG. The hemodynamic changes did not differ between sexes or between surgical and non-surgical etiologies of vocal fold paralysis. Two patients experienced profound but reversible near-syncope during the procedure. Conclusions: LEMG is a safe procedure with few immediate complications, though it may affect the patient's hemodynamic status by increasing DBP and PR. The hemodynamic monitoring is recommended so that timely intervention can be applied in case any warning sign occurs.